ANALISA PERBANDINGAN ROUTING PROTOKOL PADA WIRELESS SENSOR NETWORKS (WSNs) - Igor Novid; Delsina Faiza; Thamrin Thamrin; Winda Agustiarmi (Universitas Negeri Padang, 2019)
The development of Internet use has spurred Wireless Sensor Networks (WSNs) technology so that it becomes a widely researched and applied device. With the need to use high WSNs, the quality of features provided such as high data transfer speeds and the smallest possible disruption is something that should be available. Although some uses of WSNs do not require high speed and have a tolerance for interference, there are very few types of use. Nevertheless, routing protocols are provided to meet the types of data transfer requirements. The protocols available for each type will be analyzed and compared to find out the best performance.Keywords: data transfer, routing protocol, WSN.